Mixed-form indices: A study of their properties - Bert M. Balk (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2018)
This paper reviews the main properties of mixed-form (price) indices, in other words, chained indices which in real time behave as direct (fixed-base) indices. The European Union HICP is used as demonstration material.
Keywords: C43; E 31; 330; direct index; chained index; Lowe index; HICP